EVALUASI KEBIJAKAN PENYELENGGARAAN SISTEM PENJAMINAN MUTU INTERNAL PERGURUAN TINGGI SWASTA DI KOPERTIS WILAYAH III JAKARTA - El Amry Bermawi Putera (Universitas Nasional, 2016)
Since the enactment of Law no. 20/2003 on the National Education System, many private universities in the Region III of Kopertis Jakarta is constrained with the aspect of quality assurance. Therefore, this study aims to evaluate the policy of quality assurance - private universities in Region III of Kopertis Jakarta, as well as to acquire a new concept for the development of Public Administration based on the concept of policy evaluation of Dunn (2003 : 610) with several important criteria as follows: 1) effectiveness; 2) efficiency;3) adequacy; 4) equity; 5) responsiveness; and 6) appropriateness.Keywords: Policy Evaluation, Implementation of Quality Assurance, Private Universities.